STUDIES OF RADIO REFRACTIVE INDEX IN ASSOCIATION WITH ONSET OF MONSOON - SHARMA, R. V.; PRASAD, THAKUR; KUMAR, SHRAVAN (MAUSAM, 1993)
Variations of radio refractive index (RRI) in the lower troposphere over Bombay and Thiru-vananthapuram have been studied for the months from April to July for the years 1979 to 1987. It is seen that in most of the years, the radio refractive index at 900 hPa over Bombay increased significantly prior to onset of monsoon over Kerala (Thiruvananthapuram) and well in advance of the arrival monsoon over Bom-bay. Variation of RRI at 850 hPa level over Bombay also shows significant increase a few days later than at 900 liPa level. At higher levels no such significant changes are observed. The KM value over Thinivanantha-purain at 900 hPa or at 850 hPa does not show significant rise from pre-monsoon to monsoon months. The results show a slight decreasing trend during the same period.